G176 The National Cancer Survivorship Initiative: A National Approach to Improve the Quality of Aftercare For Survivors of Childhood Cancer. (4th June 2013) - Jenkinson, H; Gibson, F; Morris, P; Stevens, M; Hatcher, H; Glaser, A; Toogood, A; Levitt, G
Abstract : Aims: The National Cancer Survivorship Initiative [NCSI] (a partnership between the Department of Health, NHS Improvement, third sector organisations and user representatives) was established to improve the care provided for patients 'living with and beyond cancer'. It sought to work with cancer survivors to inform new models of care. The focus was to shift from traditional hospital-based models of aftercare to informed personalised patient care. The NCSI children and young people's [CYP] work stream sought specifically to design functional, cost-effective models of care underpinned by evidence. Methods: A multi-professional, multi-staged approach was used. Following an initial period of consultation, centres around England were invited to submit a service improvement project. Ten sites providing cancer care for children and young people were selected. Each site tested potential areas of change across newly-defined patient pathways, each led by an experienced clinician with service improvement input as well as significant input from young people and parents. The aim was to gather baseline evidence, test concepts and disseminate reports nationally to share learning more widely. Four centres were invited to test the models of care. Results: Evidence emerged in support of: clinical risk stratification to allow patients to receive care tailored to their individual need, personalised patient information in the form of a treatment summary and care plan, holistic needs assessment, alternative models of care to replace traditional consultant-led follow up including nurse-led care, telephone support and supported self management, psychosocial screening. Emerging from this work three different CYP patient pathways have been developed which are felt to represent gold standard care for survivors of childhood cancer at different stages of follow up and of differing risk groups. Conclusions: Comprehensive stakeholder collaboration, robust service improvement strategies and sharing of good practise and learning, have resulted in the development of evidence-based and sustainable packages of care for the growing cohort of survivors of childhood and young adult cancer. Spread and implementation are underway, using face-to-face and web-based interactive formats, to influence service delivery that can be adapted to suit local circumstances and resources.